A history of political institutions in Japan - Ishii, Ryosuke (University of Tokyo Press, 1980)
This book consists of the following many parts: the unification of the Uji and the formation of the Amenoshita-shiroshimesu-sumeramikoto, The taika reform and formation of the ritsuryo-style unified states, the growth of Shoen, the bakufu, and Shoen feudalism or middle ages 967-1467.